Performance Analysis of Solar Still along with Perforated& Non-Perforated Slabs - Nayak, Jhilirani; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
Analyses are executed to test the effect on the output of a modest solar by perforated & anti-perforated absorber plates. Two basic and comparable panels were constructed with a basin shape of 1.0 m x 0.7 m. The absorbent plates, all of them with low thermal/heat conductivity, are composed of three various non-metallic components, wood-mica, acrylic along with fiberglass. Caused by the insufficiency of a corrosion issue observed at the metal absorber plates, non- metallic absorber plates were selected. First, for every absorber plate without perforations, the execution of solar was still investigated. The wooden absorber board could not be employed for perforations because it could not endure the impacts of water, and it was quickly bent and swelled when water was wetted. The boards were then employed for drillings and the effect was not examined in the solar perforator plates. The wooden absorber plate could not be employed for perforations. The scientific results suggest that solar efficiency still depends heavily on the amount of water. With acrylic absorber flat without any drilling that was 2570 ml / d even lower than solar plates, the maximum productivity of 3160 ml / d was achieved. The usage of absorber plate without drilling increased the overall production by 22%-26%, whereas after drilling, productivity increased by only 6-14%. In the wood mica absorber sheet, subject of swelling along with bending was identified which makes it unbecoming for usage.